Improving Students’ Ability in Writing Narrative Text by Using Short Animated Film - Tamsah, Sabrianti S; Ybnu, Muhammad (Cendekiawan Indonesia Timur, 2022)
In this research, the researcher took the XI IPA grade of the second semester with subject consists of 29 students. This research has done by two cycles. Each cycle completed in four steps, started from planning, acting, observing, and reflecting. Indicator success of this research is if the average score of the students reaches the Minimum Completeness Criteria (MCC) 75. The result of the research is the implementation of short, animated film in teaching writing narrative text can improve the students‟ writing quality. The diagnose test got percentage 48%. Meanwhile when the learning activity in cycle I and cycle II the percentage of them are 76% and 88%. Based on the data the researcher can conclude that the short, animated film could help students to improve their ability in writing narrative text at the XI IPA grade of SMA Negeri 1 Aralle in academic year 2020/2021. and this research is success.